IMPROVING EMPLOYABILITY SKILLS OF UNIVERSITY STUDENTS: DEVELOPMENT TRENDS IN THE SYSTEM OF TEACHING MODERN LANGUAGES IN GREAT BRITAIN - Kovalenko, O.; Kaminska, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
In this article, the author addresses current views of British researches on enhancing employability skills of university students in the process of foreign languages acquisition. Thus, widening participation of graduates looking for jobs, dependence of national economic and social wellbeing on a good supply of graduates, showing that the financial sacrifices are economically worthwhile are considered to be of crucial importance for the issue of enhancing students’ employability in British labour market. In this regard, employability is construed as a range of developing attributes and skills necessary for the employment of graduates, notably developing a scope of attributes employers might demand, forming a range of skills indispensable for a career progression, demonstrating attributes that employers assume essential for the future efficient functioning of their enterprise or organization and acquiring a number of skills to develop into a lifelong learner. The general analysis of the respective activities of professional institutions engaged in the issues of employability of the graduates is presented. Thus, the UK higher education institutions run institutional-wide credit bearing courses that could be taken by any student registered. Moreover, British universities enhance employability skills with the aid of special agencies called careers services. The most effective option is integration of the respective courses into the curricula. This is deemed particularly efficient in case of foreign languages and the related studies acquisition. The list of employability skills specified by the British employers as indispensable for successful employment is cited, the role of language and speech skills is determined.